PENERAPAN DIMENSI P5 KEWIRAUSAHAAN DALAM PRAKTIK BUDIDAYA MARKISA DI SMA NEGERI 4 SUNGAI RAYA - Purnamasari, Ita; Achmadi, Achmadi; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study was conducted to determine efforts to increase students' entrepreneurial interest through passion fruit cultivation practices as an implementation of P5 entrepreneurship at SMA Negeri 4 Sungai Raya. This study uses a qualitative research approach with a case study form and the data is the result of interviews with 2 entrepreneurship teachers and 10 students of class XI A. The results showed that the dimension of working together as a whole was good but still needed coaching because there were obstacles. The independent dimension is good, students can understand what their abilities and weaknesses are and can process the information obtained and want to ask when they do not understand and can use their reasoning in making decisions during the passion fruit cultivation process. The critical reasoning dimension is good. Learners are able to process the information obtained and are willing to ask questions when they do not understand and can use their reasoning in making decisions during the passion fruit cultivation process. The creative dimension is also good, students have been able to produce derivative products from passion fruit, namely passion fruit syrup according to the teacher's direction and have ideas to find solutions when meeting problems during cultivation. In conclusion, the application of the P5 dimension of entrepreneurship in passion fruit cultivation practices was successfully applied to students at SMA Negeri 4 Sungai Raya.